2016
DOI: 10.1002/adsc.201600075
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung Synthesis of Diarylmethylamines via Palladium‐ Catalyzed Arylation of N‐Benzyl Aldimines

Abstract: An umpolung synthesis of diarylmethylamine derivatives is presented. This reaction entails a Pd catalyzed arylation of 1,3-diaryl-2-azaallyl anions, in situ generated from N-benzyl aldimines. A Pd(NIXANTPHOS)-based catalyst together with hindered silylamide bases enabled the coupling of aldimines with aryl bromides in good to excellent yields without product isomerization. Moreover, regioselectivity in the arylation of unsymmetrical 1,3-diaryl-2-azaallyl anions was studied. This method is suitable for a gram s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…1215 Under these conditions, deprotonation of the product was not observed, as judged by the absence of isomerized product (ArAr′C=NCHPh 2 ). 19,29 Key to preventing product deprotonation was the use of hindered bases [MN(SiMe 3 ) 2 (M = Li, Na)] at room temperature.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1215 Under these conditions, deprotonation of the product was not observed, as judged by the absence of isomerized product (ArAr′C=NCHPh 2 ). 19,29 Key to preventing product deprotonation was the use of hindered bases [MN(SiMe 3 ) 2 (M = Li, Na)] at room temperature.…”
Section: Resultsmentioning
confidence: 96%
“…Our team, 1215 and others, 1621 have been interested in the synthesis of amines via an umpolung approach involving the functionalization of 2-azaallyl anions. Recently, we reported the synthesis of both allylic amines and enamines through the transition-metal catalyzed arylation of 1,1-diphenyl-3-arylallyl-2-azaallyl anions (shown retrosynthetically in Figure 1a, path a).…”
mentioning
confidence: 99%
“…A long alkyl chain was introduced onto the P m PV backbone to assure the resulting polymer P1 has good solubility in common organic solvents. Initial reactions were conducted in 24-well plates on 10 µmol scale by adapting small molecule high-throughput experimentation (HTE) 41 48 techniques to polymerizations (see Supplementary Method, High-Throughput Experimentation screenings for polymerization for full details). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 These intermediates react with a variety of electrophiles resulting in C-C bond formation (Scheme 1A). 4,[7][8][9][10][11][12] Recently, however, this umpolung reagent was found to activate electrophiles through one-electron processes (Scheme 1B). Using EPR spectroscopy, computational studies, and radical trapping experiments, our team demonstrated the activation of aryl, alkyl, and vinyl halides through single electron transfer (SET) pathways.…”
Section: Introductionmentioning
confidence: 99%